Strengthening of structures with bacterial concrete for effective crack repair and durability enhancement - Syed Riyaz; Pollayi Hemaraju (Journal of the Mechanical Behavior of Materials)
This study explores the impact of bacterial solutions on the performance and microstructural properties of concrete mixes. Incorporating up to 10% bacterial solution demonstrated significant improvements in the dynamic modulus of elasticity for both M40 and M20 grade concrete mixes, particularly when crushed stone sand was used in place of river sand. Microstructural analyses conducted after 28 days of curing confirmed the formation of calcite (calcium carbonate) in all bacterial concrete samples. Advanced investigations using X-ray diffraction and scanning electron microscopy revealed enhanced production of calcium silicate hydrate gel and non-expansive ettringite in bacterial concrete mixes containing 10% bacterial solution, leading to superior compressive strength. Energy-dispersive X-ray analysis further highlighted an increased calcium content, correlating with the presence of calcite. The findings underscore the potential of bacterial solutions to enhance the strength, durability, and longevity of concrete structures through improved microstructural composition. From the microstructural analysis, it has been derived that calcite contributed more to the improved strength and longevity of the bacterial concrete specimens.